Storm time duskside equatorial current and its closure path. Issue 9 (12th September 2013) - Dubyagin, S.; Ganushkina, N.; Apatenkov, S.; Kubyshkina, M.; Ohtani, S.‐I.; Singer, H.; Liemohn, M.
Abstract : [1] We study the closure path of the equatorial current which flows on the duskside in the inner magnetosphere during the moderate two‐dip storm on 22 July 2009. This work was motivated by the result obtained in Tsyganenko and Sitnov (2007) that the prominent part of the duskside equatorial current might close through the dayside magnetopause during magnetic storms. Assuming the electric current conservation, we compared the value of the total downward region 2 current with the intensity of the equatorial current on the duskside to infer what part of the latter closes through the ionosphere. The estimates of the intensity of the equatorial current were based on the THEMIS and GOES magnetic field measurements in the vicinity of geosynchronous orbit. It was found that the duskside equatorial current intensifies simultaneously with Sym‐H ∗ decrease. However, unlike the conventional partial ring current, it occupies the region of the highly stretched magnetic configuration (magnetic field inclination ∼24° at r =5.4 R E ). At the same time, the magnetic field measurements onboard three DMSP satellites showed that the local time distribution of the storm time region 2 currents preserves the pattern typical for more quiet periods with upward (downward) current in the prenoon (afternoon) sector. The peak intensities of the downward region 2 current were recorded within 1 h from the Sym‐H ∗ minima in the vicinity of the dusk meridian. The peak values of the total downward region 2 current were found to be within 5–5.8 mA, while the intensity of the equatorial current at R ≈5.4–6.6 R E was found to be 0.8–1.7 mA per 1 R E . Keeping a current continuity, the radial extent of the partial ring current is estimated as 3.4–6 R E . This indicates that most of the duskside current was diverted to the ionosphere during the main phase of this storm. Key Points: Main phase duskside current occupies region of stretched magnetic configuration MLT distribution of storm R2 currents preserves pattern typical for quiet time Most of main phase duskside current was diverted to ionosphere via R2 currents